ANALISA KESIAPAN SEKTOR PANGAN NASIONAL DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN MELALUI PRORGAM HAZARD ANALYSIS AND CRITICAL CONTROL POINT (HACCP) - Gunawan Widjaja; Vivin Caronia (Cross-border, 2018)
With the existence of the Asean Economic Community (MEA) in 2015 where the free trade of ASEAN countries begins to be implemented, the demands for the quality of processed products will also increase. If the quality of local products is not able to compete with imported products, then Indonesia will not be able to survive in free trade. The application of food safety in Indonesia is still considered not guaranteed. One way to ensure food safety is the implementation of the HACCP (Hazard Analysis and Critical Control Point) program on products, which is a hazard analysis and control of critical points of the production process. With the implementation of HACCP on local products, it is hoped that it will increase confidence in the safety of processed foods so that it will indirectly promote trade and the stability of the national food business and increase the competitiveness of the national food sector in the face of free trade.